Coordination under uncertain conditions: An analysis of the Fukushima catastrophe - Masahiko Aoki; Geoffrey Rothwell (Asian Development Bank Institute (ADBI), 2011)
This paper analyzes the impacts of the 11 March 2011 earthquake and tsunami at the Fukushima nuclear power plant in Japan, which were amplified by a failure of coordination across the plant, corporate, industrial, and regulatory levels, resulting in a nuclear catastrophe, comparable in cost to Chernobyl. It derives generic lessons for industrial structure and regulatory frame of the electric power industry by identifying the two shortcomings of a horizontal coordination mechanism: instability under large shock and the lack of defense in depth. The suggested policy response is to harness the power of open-interface-rule-based modularity by creating an independent nuclear safety commission and an independent system operator owning the transmission grids in Japan. We propose a transitory price mechanism that can restrain price volatility while providing investment incentives.
Keywords: L22; L43; L94; 330; Überschwemmung; Erdbeben; Kernenergie; Katastrophenschaden; Japan